2023
DOI: 10.1115/1.4062219
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Body Hydrodynamic Interactions in Fish-Like Swimming

Abstract: Many animals in nature travel in groups either for protection, survival, or endurance. Among these, certain species do so under the burden of aero/hydrodynamic loads, which incites questions as to the significance of the multi-body fluid-mediated interactions that are inherent to collective flying/swimming. Prime examples of such creatures are fish, which are commonly seen traveling in highly organized groups of large numbers. Indeed, over the years, there have been numerous attempts to examine hydrodynamic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Research aimed at a single locomotor has found that mechanized fins, wings, or foils driven to flap share with biological propulsors many aspects of the flows, forces, energetics, and dynamics 12 , 25 , 26 . Further, recent experimental, computational, and modeling work focusing on multi-propulsor interactions make this system a promising candidate for the study of high- collective locomotion 27 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Research aimed at a single locomotor has found that mechanized fins, wings, or foils driven to flap share with biological propulsors many aspects of the flows, forces, energetics, and dynamics 12 , 25 , 26 . Further, recent experimental, computational, and modeling work focusing on multi-propulsor interactions make this system a promising candidate for the study of high- collective locomotion 27 38 .…”
Section: Introductionmentioning
confidence: 99%